The Good, the Bad, and the Ugly: in search of gold standards for assessing functional genetic screen quality. Issue 6 (June 2014) - Evers, Bastiaan; Bernards, Rene; Beijersbergen, Roderick L
Abstract : Variable screen quality, off‐target effects, and unclear false discovery rates often hamper large‐scale functional genomic screens in mammalian cells. Hart et al (2014) introduce gold standard reference sets of essential and non‐essential genes, aiming at standardizing the analysis of genome‐wide screens. This work provides a framework to compare both the quality and analysis methods of functional genetic screens. Abstract : Variable screen quality, off‐target effects and unclear false discovery rates often hamper large‐scale functional genomic screens. Hart et al (2014) introduce gold standard reference sets of essential and non‐essential genes, aiming at standardizing the analysis of genome‐wide screens.